Development of an Electrochemical Cell for In Operando Characterization of Lithium/Electrolyte Interface Using X‐Ray Total Reflection. Issue 9 (29th January 2022) - Fujii, Kairi; Kibino, Keisuke; Kimura, Koji; Yoshii, Kazuki; Kiuchi, Hisao; Hirano, Tatsumi; Takabayashi, Yasuhiro; Sakaebe, Hikari; Hayashi, Kouichi
Abstract : A cell dedicated to the characterization of the electrolyte side of the Li/electrolyte interface is developed. The reflected X‐rays from the electrolyte side of the Li/electrolyte interface are measured using the developed cell. The total reflection X‐ray of the Li/electrolyte interface is successfully detected, and the critical angle is near the calculated value. In addition, the critical angle after the application of current is also in good agreement with the calculated value. Furthermore, grazing‐incidence X‐ray scattering measurements show characteristic signals that may reflect the structural change of the electrolyte, resulting from the redox reaction at the interface region. Small changes are captured in the scattering pattern of the electrolyte in the interfacial region caused by oxidation and reduction. Abstract : A new cell of a lithium metal battery is developed for an in operando characterization of the electrolyte side of the Li/electrolyte interface using X‐ray total reflection. Small changes are captured, due to charging and discharging, in the interface‐sensitive scattering pattern. This achievement is an important step toward comprehensive understanding of electrochemical reactions in Li/electrolyte interfaces at atomic level.